Penguatan Benteng Spiritual Pekon Marga Mulya : Pendampigan Anggota Remaja Islam Masjid (Risma) Sebagai Pengajar TPA Dimasa Pandemi Covid-19 - Baharudin, Baharudin; Fiteriani, Ida; Kriani, Rezi; Hunaifi, Abdul Aziz (Universitas Nusantara PGRI Kediri, 2021)
Community service with a mentoring approach is one of the alternative research methods for community empowerment action studies. The mentoring approach can create more fun and foster active community participation. The purpose of community service is to equip RISMA members to have the skills and expertise to read the Qur'an as TPA teachers and the spiritual fortress of the Pekon Marga Mulya community, Tanggamus Regency, Lampung Province. The mentoring method uses Participatory Action Research (PAR). The subjects assisted by RISMA members were 20 people. This mentoring approach uses 6 steps, namely planning, taking action and observing, doing reflection, doing re-reflection, taking action and observing and reflecting. The assistance results show that the ability to read the Qur'an as a TPA teaching staff for RISMA Members has proven to be effective in increasing. Based on the initial conditions, having the ability to read the Qur'an is quite good, namely obtaining an average score (62.6%) and it was successfully increased after mentoring to become (81.82%) in the very good category. These results inform an effective mentoring model in improving the ability to read the Qur'an as a TPA teaching staff and the religious spiritual fortress of the Pekon Marga Mulya community. The selection of community-based service approaches is good and appropriate and makes it easier for RISMA Members to understand the knowledge provided. This condition illustrates that service is in line with educational goals. In line with that, this service can be used as an alternative for stakeholders to equip the skills of RISMA Members, especially during the COVID-19 pandemic